(untitled) (Journal of Advanced Research in Social Sciences, 2023)
The affective computing approach of artificial intelligence has made it possible for machines to not only think, behave and communicate like humans, but to also emote like humans. This dimension of AI is substituting human capacities due to its benefits in diverse spheres of life. While studies abound in the comparison between AI and human intelligence in terms of their cognitive capacities, very few have focused on the emotional aspect. This study therefore, utilized secondary data by reviewing empirical studies to examine the implications of AI in the emotional aspects of human communication. The study is anchored on basic emotion theory and technological determinism which enunciate the fundamentals of emotional AI and its effects. The paper argues that the complexity and subjectivity of human intelligence and emotion cannot be adequately replicated by AI as it lacks innate emotion and the ability to understand abstracts. It recommends media literacy skills for users and ethical guidance for technological companies designing AI to ensure it is less detrimental to human and the society.